Creating Shared Value in Support of Coffee - Nasha Acacia Almira; Effy Zalfiana Rusfian (International Journal Labs, 2023)
This study offers a comprehensive analysis of Nescafe's Corporate Social Responsibility (CSR) strategy within the context of Indonesia. Employing a literature review methodology, the research draws on an extensive range of sources, including prior journal articles and official Nescafe company reports, to unravel the intricacies of Nescafe's CSR approach. The focal point of this examination is the globally recognized multinational coffee producer, Nescafe. The research involved an exhaustive review of eight selected journal articles that delve into Nescafe's CSR initiatives and sustainability reports. The outcomes of this analysis unveil a holistic perspective on Nescafe's sustainability strategy in Indonesia. A central facet of this strategy is dedicated to addressing pressing environmental concerns, chiefly marked by the ambitious objective of reducing greenhouse gas (GHG) emissions by an impressive 35% per metric ton of soluble coffee. This reduction is meticulously monitored through regular assessments encompassing critical factors such as water resources, soil quality, and biodiversity. Notably, the paramount goal of Nescafe's CSR program in Indonesia is to support local coffee farmers, enabling the distribution of Nescafe coffee products throughout the country. In a symbiotic relationship, Nescafe leverages the strengths of local farmers to source raw materials while simultaneously imparting advanced production technologies, ultimately enhancing the quality of the products. The depth of Nescafe's commitment to CSR is manifest through a plethora of documented programs and activities, all thoughtfully disseminated via the company's official website. This study provides a valuable lens through which to understand Nescafe's strategic CSR and sustainability efforts, underscoring the company's role in fostering environmental sustainability, uplifting local communities, and elevating product quality in Indonesia.